2022
DOI: 10.3390/foods11050701
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Olive Leaf Extract as a Functional Ingredient in Yoghurt Production: The Effects on Fermentation, Rheology, Sensory, and Antioxidant Properties of Cow Milk Yoghurt

Abstract: Background: Yoghurt has been traditionally consumed for its high nutritional value and health-promoting benefits. The addition of plant extracts as a source of phenolic compounds and bio-flavonoids has attracted much attention recently since milk and dairy products are deficient in these health-protecting components. Accordingly, olive leaf extract (OLE) has been considered due to the presence of bioactive compounds, primarily polyphenols. Thus, the aim of this research was to investigate the possibility of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In general, it was found that the addition of OLE significantly (p < 0.0001) increased the TP in all cheese samples as well as in the remaining whey, regardless of the coagulation method (p > 0.05). The obtained results are consistent with previously published data [8,[42][43][44][45]. The increase in TP corresponds to the increase in the effective concentration of the added OLE, except in the sample EM 25, where the TP was the highest, probably due to the variations in the dewatering process.…”
Section: Textural Parameters Of Ole Supplemented Cheese Curdssupporting
confidence: 92%
See 3 more Smart Citations
“…In general, it was found that the addition of OLE significantly (p < 0.0001) increased the TP in all cheese samples as well as in the remaining whey, regardless of the coagulation method (p > 0.05). The obtained results are consistent with previously published data [8,[42][43][44][45]. The increase in TP corresponds to the increase in the effective concentration of the added OLE, except in the sample EM 25, where the TP was the highest, probably due to the variations in the dewatering process.…”
Section: Textural Parameters Of Ole Supplemented Cheese Curdssupporting
confidence: 92%
“…An increase in AA was also observed in the whey remaining after acid coagulation, which was significantly higher compared to enzymatic coagulation (p < 0.0001), correlating with the results of the TP (Figure 3). Although the influence of OLE on the AA of cheese has not been studied in detail, some previous studies have also shown that the addition of OLE leads to an increase in the antioxidant activity of yogurt [8,19] and kefir [54]-dairy products that are also produced by acid coagulation.…”
Section: Antioxidant Activity (Aa)mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Ghasempour et al (2012) that of Amirdivani and Baba (2013), who reported that adding 2% green tea extract to yogurt reduced its apparent viscosity. Barukčić et al (2022) reported that the presence of olive leaf extract led to a reduction in yogurt viscosity, which was more or less proportional to the olive leaf extract concentration. These reports reveal the effect of plant extracts related to plant type and their concentration (Haji Ghafarloo et al, 2019).…”
Section: Viscosity Of Yogurt Measurementsmentioning
confidence: 99%